Digital Innovations in Pneumonia Care: A Mini Review - Tripathy, Snehasish; Negi, Sapna; Mathur, Ankita; Mehta, Vini (National Journal of Community Medicine, 2024)
Introduction: Pneumonia is a severe respiratory disease threatening public health and requires timely and accurate diagnosis and early intervention for effective treatment. The emergence of telemedicine during COVID-19 has offered new solutions to solve health problem. This review examines recent studies focusing on effectiveness of telemedicine intervention in pneumonia care. Methods: We systematically searched five databases to retrieve original research that addressed telemedicine's use in pneumonia diagnosis, treatment, monitoring, or patient assistance. Two independent reviewers performed screening to confirm alignment with inclusion criteria. The findings were synthesised narratively. Results: A total of five studies were included in the review. The interventions across studies were telephonic follow-ups, Smartphone-based algorithm for diagnosing pneumonia, telemedicine set-up at patients' homes and Interactive videoconferencing. The findings suggest that telephone consultation is effective for patients with low-risk respiratory infections and may be more effective in early diagnosis of pneumonia patients. Conclusion: The planning for work in telemedicine, whether in regulations or private practice, is necessary to ensure the quality, safety, and consistency of telemedicine practices. The use and availability of telemedicine services, especially in rural areas and on mobile phones, must be expanded to reduce problems in the region.